Adaptive Control Of Grid Integrated Photovoltaic Using Recurrent Neural Network - Kumar, R. Senthil; S., Prabakaran; Selvan, S. Sentamil (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The Photovoltaic (PV) demand is increasing day by day globally. To meet the demand PV is generally connected to the distribution grid. To achieve higher efficiency of the PV integrated distribution grid, this paper proposes an algorithm named Recurrent Neural Network (RNN) for the control of the PV integrated distribution grid system. This algorithm controls the Voltage source converter (VSC) by aiming for harmonic mitigation, load balancing and other power quality problems. This algorithm focuses to deliver maximum power on the grid side VSC. The proposed technique is designed and simulated in a MATLAB environment using SIMULINK. The results confirm that the Total Harmonic Distortion is reduced as recommended by the IEEE-519 standard.